Eufemisme sebagai Instrumen Ideologis dalam Wacana Kebijakan Makan Bergizi Gratis - Ulfa Kurniasih; Azizatul Khairi (Universitas Ahmad Dahlan, 2026)
The Free Nutritious Meal Program (MBG), which was launched on January 6 2025 with an allocation of IDR 71 trillion, is the largest nutritional intervention in Indonesian history. But on March 31, 2026, the government announced a reduction in distribution from six to five days per week—a policy consistently communicated using the phrase